Route of fire: the marketing of low media coverage in the face of a large number of fires in the semi-arid region of Piauí (Research, Society and Development, 2022)
Thousands of miles of vegetation are destroyed every year around the world. In Piauí, the incidence of fire outbreaks occurs very frequently in the warmer months, mainly because the state has its vegetation predominantly of cerrado and caatinga. Thus, the research aims to understand about the fires in the semi-arid region of Piauí and these are highlighted in the news linked by the media. For research used in the material and methods, a survey at INPE, as well as research on news in newspapers relevant to the topic, the methodological procedure was descriptive, qualitative and bibliographic. High incidence of fires and fires in the state, the media does not give much emphasis, it was seen during the news relevant to the subject, that is, the media does not emphasize in its news as fires in the semi-arid Piauí